Mengungkap Perilaku Inovatif 3 Etnis Wanita Pedagang Di Surabaya - Tri Siwi Agustina (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2014)
Innovative behavior is one of the requirements to survive in the field that are hard, competitive, challenging, high-risk and speculative as world trade. Similarly, the existence of a trading business carried on women can not be separated from the innovative behavior, whereas on the other hand women are also faced with the primary responsibility of the family. That directs human behavior to act not apart of the culture surrounding the actors. Based on this, presumably interesting to study about differences in innovative behavior of women traders Javanese, Madurese and Chinese in Surabaya. Sources of data obtained by distributing questionnaires and conducting interviews in 394 women traders convection type in one of the wholesale center in the city of Surabaya, which was selected as the study respondents. This study is a quantitative research method research design ANOVA (F-test). The findings of this research are innovative behavioral differences merchant woman of Javanese, Madurese and Chinese.